Describing Disclosure of Cybervictimization in Adolescents from the United Kingdom: The Role of Age, Gender, Involvement in Cyberbullying, and Time Spent Online. Issue 1 (2nd January 2022) - Betts, Lucy R.; Spenser, Karin A.; Baguley, Thom
ABSTRACT: Disclosing experiences of cybervictimization is an important first step in many anti-bullying interventions. Gender, age, cybervictimization experiences, cyberbullying behaviors, and time spent online were examined as factors that describe: (a) disclosing cybervictimization and (b) perceptions of helpfulness following disclosure. The sample comprised 750 (384 boys and 365 girls, M age = 12.57 years, SD age = 1.25 years) 11- to 15-year-olds recruited from two schools. Participants completed self-report measures of cybervictimization experiences, cyberbullying behaviors, intent to disclose cybervictimization, who they thought would be helpful following disclosing cybervictimization, and technology use. Over 88% of the sample reported that they would disclose cybervictimization. Girls and those experiencing low levels of cybervictimization reported they would disclose cybervictimization. Those who were older, and girls reported that they thought friends would be helpful following a disclosure of cybervictimization, whereas those who were younger reported that parents and the police would be helpful. A Gaussian graphical model was used to further explore perceptions of helpfulness following disclosure of cybervictimization and highlighted a complex pattern between targets. The findings add to the growing evidence of the complexity around adolescents' propensity to disclose experiences of cybervictimization which has implications for anti-bullying interventions.